(untitled) (Proceedings of Southern Federal University. Philology, 2015)
This article gives an uncommon interpretation of works by L. Panteleev, which allows to pay attention to unexplored in the Soviet era ideas, themes, motifs, images of the writer, as well as to look differently at the known texts. Focus is concentrated on considering of myth and poetic “layer” of works by L.Panteleev. The paper presents the archetype of the Father, which is implemented in the religious and gender contexts. It is proved the importance of this archetype in the literary heritage of the writer. Special attention is paid to the time of action of the analyzed works which reflects the era of social collapses, wars and revolutions (novel “The Republic SHKID”, story “Portrait”), and in peacetime (diaries of L. Panteleev “Our Masha” story “Caruseli” autobiographical novel “Lenka Panteleeva”, story “Nastya”), which helps to understand and trace the relationship of historical time with the archetype of the Father. Of particular interest is the study of the feminization of the male characters in the author’s mind, which makes it possible to see various embodiments of the archetype of the Father, and to present the most complete realization of the idea of fatherhood. Keywords: archetype, idea of fatherhood, father, gender, feminization. Batova Olga Sergeevna - post-graduate student of literature dpt. Volgograd state social-pedagogical university. E-mail: reutolga@yandex.ru